A Review on K nearest Neighbour Classification Technique in Machine Learning - Dr. G. Vijaya Lakshmi (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Classification is a Supervised Learning technique which is used to predict the correct category from the given input features. Logistic regression, decision trees, random forests, support vector machines (SVM), naive bayes, and K-nearest neighbors (KNN) are some of the several classification techniques.. This paper discusses the KNN classification technique, which uses the similarity measure of previously stored data points to classify new data points.